ChIP-Seq analysis of the adult male mouse brain after developmental exposure to arsenic - Tyler, Christina R. (Data Brief, 2015)
Exposure to the common environmental contaminant arsenic impacts the epigenetic landscape, including DNA methylation and histone modifications, of several cell types. Developmental arsenic exposure (DAE) increases acetylation and methylation of histone proteins and the protein expression of several chromatin-modifying enzymes in the dentate gyrus (DG) subregion of the adult male mouse brain [26]. To complement and support these data, ChIP-Seq analysis of DNA associated with trimethylation of histone 3 lysine 4 (H3K4me3) derived from the adult male DG after DAE was performed. DAE induced differential H3K4me3 enrichment on genes in pathways associated with cellular development and growth, cell death and survival, and neurological disorders, particularly as they relate to cancer, in the adult male brain. Comparison of H3K4me3 enrichment in controls revealed mechanisms that are potentially lacking in arsenic-exposed animals, including neurotransmission, neuronal growth and development, hormonal regulation, protein synthesis, and cellular homeostasis. New pathways impacted by arsenic include cytoskeleton organization, cell signaling, and potential disruption of immune function and warrant further investigation using this DAE paradigm in the mouse brain.